PERANAN BANQUET DALAM MENDUKUNG OPERASIONAL FOOD AND BEVERAGE DI UTC DAGO HOTEL BANDUNG - Syahlevie, Nor; Nirwani, Ayulia (Jurnal Perhotelan dan Pariwisata, 2025)
Banquet is a part of the Food and Beverage Department which is tasked with handling activities .The services in the Food and Beverage Department are generally divided into two, namely, Food and Beverage Service and Food and Beverage Product. Food and beverage Service is divided into several sections, one of which is the Banquet Section. The term Banquet is the service of an event that has been ordered and planned in advance, including food and drink services, space and complete equipment needed at a certain time. This includes meetings, conferences and other events (MICE). Banquet services play a very important role because they serve a large number of guests at the same time. The role of the Banquet Section in supporting the operations of the Food and Beverage Department at UTC Dago Hotel Bandung is as a source of income Hotel, improve the hotel's reputation, and increase guest satisfaction in terms of service. Furthermore, efforts are made to improve Banquet Section services at UTC Dago Hotel Bandung by improving service quality, quality products, cleanliness of premises and equipment, and a pleasant atmosphere. The problems faced by the Banquet Section in operations are the increase in guests or participants, equipment and extra services.